Kegagalan dan Keberhasilan Pasca Proses Pemekaran Daerah Provinsi Kepulauan Riau - Syaihidina Hefir; Indah Utami; Muhammad Nursyawal; Muhammad Aidil Zulfa; Arya Pramudia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Regional expansion in Indonesia, especially in the Riau Islands, is a strategic effort to improve public services and the quality of life. Riau Islands, is a strategic effort to improve public services and accelerate post-1998 reform development. Accelerate post-reform development in 1998. Although it is expected to bring government closer to the people and improve welfare through decentralization through decentralization, the reality is that around 78% of the resulting regions failed to achieve their desired goals. Have failed to achieve their desired goals. This failure caused by various factors, including administrative unpreparedness, high fiscal dependency, political conflicts of interest, and lack of community participation. Community participation. However, this article also highlights examples of successes that show that with local government commitment and commitment of local governments and community support, some regions have been able to improve the quality of public services and optimize their and optimally utilize the potential of natural resources. Factors that influencing this success involve local government commitment, natural resource management, community support, infrastructure availability, and central government policies. This article aims to explore factors contributing to the failure and success of post-regional expansion in the Riau Islands and its impact on society and regional development. With a deeper understanding of this issue, it is hoped that more effective policies can be formulated more effective policies in the management of new autonomous regions to face future development challenges. To face future development challenges.